Optic disc pit with multiquadrant peripapillary retinoschisis and choroidal coloboma. Issue 7 (15th July 2021) - Sachan, Anusha; Rani, Deeksha; Lata, Suman; Chawla, Rohan
Abstract : An 18-year-old man presented with decreased vision in the right eye (OD) noticed for 1 month. On examination, OD best-corrected visual acuity was 3/60 and the left eye (OS) was 6/6 with intraocular pressure of 12 mm Hg in both the eyes (OU). OD fundus revealed an inferior optic-disc-pit with macular-retinoschisis and an inferior choroidal coloboma. OS fundus was normal. On swept-source optical coherence tomography (SSOCT) radial scans, peripapillary-retinoschisis was seen not only in the macular region but in all the four quadrants. To the best of our knowledge, no such case has been reported of optic disc pit with multiquadrant peripapillary retinoschisis and choroidal coloboma coexisting in the same eye. SSOCT radial scans can help detect subclinical retinoschisis as in this case.